Leisure Time Activities and Mental Health in Informal Dementia Caregivers. Issue 2 (11th June 2015) - Schüz, Benjamin; Czerniawski, Alana; Davie, Nicola; Miller, Lisa; Quinn, Michael G.; King, Carolyn; Carr, Andrea; Elliott, Kate‐Ellen J.; Robinson, Andrew; Scott, Jenn L.
<x xml:space="preserve">Abstract</x> Objectives Dementia prevalence and the demand for dementia care are increasing. Informal caregiving accounts for a large proportion of dementia care, but can come at high cost for caregivers. Informal dementia caregivers are at higher risk for mental health problems than the general population. This study examines whether perceived change in leisure activities is one working mechanism linking stress and burden experience in dementia caregiving to lower mental health (depressive symptoms, anxiety symptoms, and reduced satisfaction with life), and whether there are group‐based leisure activities that can buffer this detrimental effect. Methods A total of 346 informal Australian dementia caregivers (88.15% female, age 18–82 years) participated in an online study. Results Mediation and moderation analyses using multiple regression demonstrated that perceived changes in leisure activities linked caregiving stress and burden to lower mental health, and that membership in groups engaging in affiliation or social activities attenuates negative effects of caregiving. Conclusion Informal dementia caregivers benefit from satisfying leisure activities. In particular, engaging in social activities and self‐help groups buffered the negative impact of caregiving.